Extraction, modification, characterization and metal adsorption properties of cellulose obtained from banana stem and bamboo stem - Chandrawansha, N.P.S.I.; Arasaretnam, S. (University of Jaffna, 2024)
Banana stem and bamboo stem can be known as few of the agricultural residues in the agricultural sector, which are inexpensive, readily available, environmentally friendly, and recyclability. Cellulose was extracted from the banana stem and bamboo stem by using the following chemical processes: Soxhlet extraction, alkali treatment and bleaching process respectively. The cellulose obtained after the above processes was treated with glycine (10 %, 20 %, and 30 %, 40 % and 50 % w/v) in NaOH solution to synthesize cellulose-glycine hydrogel series. The synthesized hydrogels were treated with mono, di and trivalent cation solutions to study the metal adsorption capacities with different compositions of hydrogel prepared. Then the two samples and untreated cellulose obtained from both banana and bamboo stems were characterized using FTIR spectroscopy.
Keywords: Cellulose; Hemicellulose; Lignin; Hydrogel; Glycine; Metal adsorption